Unraveling the Determinants of Dengue Fever Incidence in Indonesia: A Systematic Review of Environmental and Behavioral Factors - Agung Waskito; Agung Sutriyawan; Agung Romilian; Darmanto Darmanto; Sri Achadi Nugraheni (Public Health of Indonesia)
Background: Dengue Hemorrhagic Fever (DHF) is a significant public health issue in Indonesia, with an increasing incidence rate. Various factors, including environmental, social, and behavioral aspects, contribute to DHF.